Use of Analytic Hierarchy Process (AHP) For Selection of Corrosion under Insulation (CUI) Critical Inspection Locations - Abdull Kadir, Nor Amirah (2018)
The issue of leakage due to corrosion under insulation, CUI has become a normal frequent problem arise in the industry especially in petrochemical plant. In couple of decades, reports have shown that every single leakage that occur might worth of billion dollars. Since corrosion is a phenomenon that occur naturally, it is impossible to totally brush it off. This project is intended to select system with the most CUI critical inspection location. By selecting the system which most susceptible to CUI, inspection strategies for CUI cases can be properly planned; thus, serious cases involving CUI could be minimized. This study is accomplished by implementing the method of Analytic Hierarchy Process in which the factors are being further analysed. Microsoft Excel is used to analyse the inspection data and results of carbon steel piping which is gathered from Plant Rejuvenation and Revamp 2 (PRR2) project, PETRONAS Gas Berhad. The accomplishment of this project would help in development of a better plan and strategy for inspection purposes.